2020
DOI: 10.3329/ralf.v7i2.48874
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of Shrimp Farming in Satkhira, a Southwestern District of Bangladesh

Abstract: Shrimp has become one of the most important export products in recent decades due toincreasing international demand. Shrimp farming is performing significant role in thelivelihoods of rural people of southwestern part of Bangladesh which is considered thecore areas for shrimp farming. To continue the trend of exporting shrimp worldwide it isvery much needed to be familiar with the current culture practices with the precautionstaken by the shrimp farmers. A total of 30 shrimp farmers in Shyamnagarupazilla ofSat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Bamboo traps (standard 2 ft x 2.5 ft x 2 ft) with bait (small shrimps) are set up 8-10 feet intervals at peripheral dikes. In case of less catch by Gai, trap method, cast net or seine net is used (Alam and Phillips, 2004;Mamun et al, 2020).…”
Section: Harvesting Methods and Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo traps (standard 2 ft x 2.5 ft x 2 ft) with bait (small shrimps) are set up 8-10 feet intervals at peripheral dikes. In case of less catch by Gai, trap method, cast net or seine net is used (Alam and Phillips, 2004;Mamun et al, 2020).…”
Section: Harvesting Methods and Gradingmentioning
confidence: 99%
“…Farms containing 1-5 ha, 6-10 ha and >10 ha area are considered as small, medium and big farms, respectively (Islam et al, 2005). Most farmers own small farms (Mamun et al, 2020). Height and width of dike vary from 0.4-1.2 m and 0.2-0.7, respectively.…”
Section: Pond Managementmentioning
confidence: 99%
“…Mahamud (1998) and Das (1993) however, mentioned about the problems of shrimp farms, which were: the lack of credit, lack of scientific methods and poor quality PL. Al- Mamun et al (2020) found the problems faced by the shrimp farmers were: high mortality, poor water quality and low market price.…”
Section: 6 Problems Faced By the Farmers During Farming Systemmentioning
confidence: 99%